2019
DOI: 10.21831/cp.v38i2.21556
|View full text |Cite
|
Sign up to set email alerts
|

Kawruh Pamomong: Children Education Based on Local Wisdom in Yogyakarta

Abstract: Character education is the fundamental thing for one's future. In Indonesia, especially in Yogyakarta, the education of local wisdom based is Kawruh Pamomong. It is to educate children based on the truthfulness, love/passion and beautifulness or gracefulness. This research aims at studying and mapping the family education based on local wisdom Kawruh Pamomong Ki Ageng Suryomentaram in the sub-village of Balong of Timbulharjo Village in the sub-district of Sewon, Bantul Regency of Yogyakarta. Balong is a sub-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…This character education is fundamental to the future of students. Therefore, local wisdom education that can teach positive values such as honesty needs to be applied starting from the family, school, and community environment (Gularso et al, 2019). The value of honesty as a student character developed through the 2013 curriculum can be integrated through the learning process in all lessons, so that dishonest actions that can be done by some students such as cheating while working on assignments or exams can be avoided (Sitorus et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This character education is fundamental to the future of students. Therefore, local wisdom education that can teach positive values such as honesty needs to be applied starting from the family, school, and community environment (Gularso et al, 2019). The value of honesty as a student character developed through the 2013 curriculum can be integrated through the learning process in all lessons, so that dishonest actions that can be done by some students such as cheating while working on assignments or exams can be avoided (Sitorus et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Gularso et al's research, found that the counselor's knowledge 'correct and clean' in teaching within the family sphere was the responsibility of the father and mother. Meanwhile, the counselor's knowledge 'beautiful' is primarily to be taught by father [16].…”
Section: Poetry and Character Education Valuesmentioning
confidence: 99%
“…However, in this study, the application of literacy learning is to improve students' learning outcomes of science and social attitudes and the renewal that is done is to integrate literacy learning with insight into Balinese culture. The success of national education can be achieved by grasping the character of citizens including those related to tradition or culture (Gularso et al, 2019) Analysis of the findings from Muskania & Wilujeng (2017) study showed that science learning tools based on project-based learning developed in the form of RPP, LKPD, and authentic assessment are appropriate to be used with excellent criteria under the results of validation and testing in the science learning process at the junior high level. The developed learning tool can equip the foundational knowledge of individual students on ICT literacy with excellent criteria.…”
Section: Introductionmentioning
confidence: 99%